Your first step is wrong. Just subtract b². It should be
4b = 3b²
3b² - 4b = 0
b(3b-4) = 0
b=0 or b=4/3
b = -4/3 should immediately be seen not to work, since you have
b² + 4b = 4b²
If b is negative, there is no way you could subtract something from b² and wind up with 4b².
I have absolutely no idea how to factor the following:
b² + 4b = 4b²
I think you subtract 4b² from both sides:
3b² + 4b = 0
Then
b(3b + 4) = 0
Then
b = 0 and b = -4/3
Is this correct?
Thank you.
2 answers
Thank you Steve! I see where I made my mistake.